The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/14651858.cd010775.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment for the diagnosis of Alzheimer’s disease and other dementias

Abstract: The overall quality and quantity of information is insufficient to make recommendations on the clinical utility of MoCA for detecting dementia in different settings. Further studies that do not recruit participants based on diagnoses already present (case-control design) but apply diagnostic tests and reference standards prospectively are required. Methodological clarity could be improved in subsequent DTA studies of MoCA by reporting findings using recommended guidelines (e.g. STARDdem). Thresholds lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
0
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(202 citation statements)
references
References 51 publications
(125 reference statements)
8
176
0
18
Order By: Relevance
“…A recent review found that the MoCA had a good sensitivity, allowing detection of over 94% of individuals with dementia in all observed settings (Davis et al, 2015). The same review underlined the low specificity of the MoCA, with over 40% of normal controls being false positives when their score falls below 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review found that the MoCA had a good sensitivity, allowing detection of over 94% of individuals with dementia in all observed settings (Davis et al, 2015). The same review underlined the low specificity of the MoCA, with over 40% of normal controls being false positives when their score falls below 26.…”
Section: Discussionmentioning
confidence: 99%
“…This test has proved to be sensitive to mild cognitive deficits and to predict future cognitive decline in several cognitively impaired states, including Alzheimer's disease and dementias (see Davis et al, 2015 for complete review), Parkinson's disease (Gill, Freshman, Blender & Ravina, 2008), chronic obstructive pulmonary disease (Villeneuve et al, 2012), rapid eye movement sleep behavior disorder (Gagnon, Postuma, Joncas, Desjardins & Latreille, 2010), Huntington's disease (Mickes et al, 2010;Videnovic et al, 2010), cerebrovascular diseases (Cameron, Ski & Thompson, 2012;Cumming, Bernhardt & Linden, 2011;Pendlebury, Cuthbertson, Welch, Mehta & Rothwell, 2010;Popovic, Seric & Demarin, 2007;Schweizer, Al-Khindi & Macdonald, 2012), human immunodeficiency virus (Overton et al, 2013), traumatic brain injury (de Guise et al, 2013), and cancer (Olson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to differentiating dementia from NC. None the less, dementia diagnosis based on MoCA has recently been reviewed [32], suggesting the quality of the studies was "not good enough" to conclusively recommend its use and that a lower cut-off was likely to be more accurate. While the review reported optimal sensitivity and specificity due consideration was not given to education or variation in suggested cut-offs.…”
Section: Rationalementioning
confidence: 99%
“…Although each of these tests has been previously validated in several languages and settings [10,11,12], mostly in comparison to the MMSE, to our knowledge, few studies have directly compared the diagnostic capacity of multiple instruments in the same study. In primary care, Holsinger et al [13] compared the modified MMSE, MIS, and Mini-Cog in the diagnosis of dementia, obtaining better results with the modified MMSE and Mini-Cog, while the MMSE achieved higher specificity but lower sensitivity.…”
Section: Introductionmentioning
confidence: 99%